Social Atmosphere as Integration of Interaction Strata: Empirical Testing of the Conceptual Position - P. P. Deryugin; S. V. Boyarintseva (Дискурс)
Introduction. The sociological content of the concept of social atmosphere remains unclear, it is constantly refined and supplemented. An attempt is made to consider the social atmosphere as a set of strata of social interaction mediated to varying degrees by material, non-material and psychological (psychosomatic) factors.Methodology and sources. The conceptual theoretical and methodological positions of the study are represented by a set of ideas of M. Weber, A. Lefebvre, L. Althusser, A.V. Petrovsky,A.I. Dontsov, as well as the provisions and conclusions of interdisciplinary studies of the relationship between social processes and psychosomatics, in particular, expressed in the works of R.G. Khalitova, V.V. Vasina and others. The social atmosphere is considered as a set of strata of interactions that develop between subjects under the influence of a wide variety of factors. The authors used official statistics and secondary data for a thirty-year period of turbulent socio-economic transformations from 1990 to 2020.Results and discussion. It has been empirically confirmed that the overall mortality rate depends on the political and socio-economic events in the country. The extreme points of the take-off of mortality rates have been identified, which are the psychological reaction of people to significant socio-political events (the breakdown of the social system, a coup d'état, default). After 2000, the income of the population began to grow, but mortality did not decrease to the level of 1990. Throughout the analyzed period, the incidence rates of socially significant diseases also remain high.Conclusion. The analysis of statistical materials indicates the importance of non-material, mental-emotional determinants of public health and life expectancy, which are associated with the social atmosphere.